The role of pi-interactions and hydrogen bonds in fully protective synthetic malaria vaccine development (2017)
Analysis of our Plasmodium falciparum malaria parasite peptides’ 1H-NMR database in the search for H-bonds and ?-interactions led us to correlate their presence or absence with a peptide's particular immunological behavior. It was concluded that a 26.5 ± 1.5 Å between positions 1 to 9 of the HLA-DR?1* interacting region was necessary for proper docking of 20mer-long peptides and these MHC Class II molecules for full-protective immunity. Presence of intramolecular H-bonds or ?-interactions leading to righ-handed ?-helix or ?-turn conformation in this peptide's region induces different immune responses or none. PPIIL conformation and the absence of any intramolecular interaction thus became the first feature characterising our immune protection-inducing structures as malaria vaccine candidates. © 2017 Elsevier Inc.